PENGARUH PROPORSI TEPUNG DAUN BELUNTAS (Pluchea indica Less) DAN TEH HITAM TERHADAP SIFAT FISIKOKIMIA, SIFAT ORGANOLEPTIK, DAN AKTIVITAS ANTIOKSIDAN PRODUK MINUMAN - Halim, Maria Olivia; Widyawati, Paini Sri; Budianta, Dwi Wibawa (Widya Mandala Surabaya Catholic University, 2015)
Beluntas (Pluchea indica Less) is a plant that has been used as vegetables and medicine herb in Indonesia. Phytochemical compounds in beluntas leaves have antioxidant activity to prevent free radical that may cause degenerative diseases. One of beluntas utilization-product is functional beverage of beluntas leaves that substituted black tea. This research aimed to determine the effect of beluntas leaves powder and black tea proportion on physicochemical properties, senseory properties, and antioxidant activity of beverage product. The reasearch design used is randomized block design. Factor that will be researched is beluntas leaves powder and black tea proportion in the amount of 100:0; 75:25; 50:50; 37.5:62.5; 25:75; 12.5:87.5; dan 0:100% (w/w). The parameters observed are water content of beluntas leaves and black tea powders, phytochemical identification; physicochemical properties including color, pH, titratable acid, and turbidity; sensory properties including color, flavor, and taste; antioxidant activity using DPPH method, total phenol, total flavonoid, and iron ion reducing power. The results showed that the proportion of beluntas leaves powder and black tea significantly affected on physicochemical properties, senseory properties, and antioxidant activity of beverage product. Hue angle value ranged from 9.67-80.50; chroma value ranged from 2.66-8,36; pH value ranged from 6.04-6.74; titratable acid ranged from 14.24-64.92 mg chlorogenic acid/100 mL infusion or 7.19-64.92 mg gallic acid/100 mL; turbidity value ranged from 32.83-105.87 NTU; phenolic content ranged from 12.18-23.51 mg GAE/g sample, flavonoid content range from 2.54-9.18 mg CE/g sample, DPPH scavenging activity range from 14.95-29.60 mg GAE/g sample, dan iron ion reducing power ranged from 17.98-22.44 mg GAE/g sample. Based on the effectiveness test, the best treatment were beluntas leaves powder and black tea proportion in the amount of 25:75% (w/w).